2013
DOI: 10.3389/fgene.2012.00321
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing differential individual response to porcine reproductive and respiratory syndrome virus infection through statistical and functional analysis of gene expression

Abstract: We evaluated differences in gene expression in pigs from the Porcine Reproductive and Respiratory Syndrome (PRRS) Host Genetics Consortium initiative showing a range of responses to PRRS virus infection. Pigs were allocated into four phenotypic groups according to their serum viral level and weight gain. RNA obtained from blood at 0, 4, 7, 11, 14, 28, and 42 days post-infection (DPI) was hybridized to the 70-mer 20K Pigoligoarray. We used a blocked reference design for the microarray experiment. This allowed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…4–6) significantly involved in response to PRRSV infection in macrophages at different activation statuses. It is noteworthy that our RNA-Seq analysis using polarized macrophages revealed a dozen more significant pathways that have not been reported in previous transcriptomic analyses using PRRSV-infected tissues or cells [27][34]. Furthermore, analysis of two key signaling pathways, AMPK-mediated and epigenetic mechanisms, not only clustered the pathway-inclusive DEGs pertaining to each activation status, but also functionally validated the involvement of AMPK-mediated and epigenetic pathways in regulation of antiviral response to PRRSV infection in cells.…”
Section: Discussionmentioning
confidence: 46%
“…4–6) significantly involved in response to PRRSV infection in macrophages at different activation statuses. It is noteworthy that our RNA-Seq analysis using polarized macrophages revealed a dozen more significant pathways that have not been reported in previous transcriptomic analyses using PRRSV-infected tissues or cells [27][34]. Furthermore, analysis of two key signaling pathways, AMPK-mediated and epigenetic mechanisms, not only clustered the pathway-inclusive DEGs pertaining to each activation status, but also functionally validated the involvement of AMPK-mediated and epigenetic pathways in regulation of antiviral response to PRRSV infection in cells.…”
Section: Discussionmentioning
confidence: 46%
“…Differences in animal age were not important, as we obtained similar results with 6 week-old and 1 year-old blood donors. However, the genetic of the pigs could possibly play a role since differential expression genes, especially IFNA, have been highlighted in phenotypic pig groups in response to PRRSV [41]. Another difference compared to the data from Calzada-Nova et al could be the methodology and cell isolation procedures.…”
Section: Discussionmentioning
confidence: 93%
“…Initial work using microarrays showed a number of genes that were differentially expressed between animals with high and low host response to PRRS (Arceo et al, 2013). Using microarray gene expression profiles, Schroyen et al (2015) identified differences in blood RNA patterns in early responses to PRRSV infection between pigs with extreme phenotypes or with a different WUR genotype.…”
Section: Additional Gene Expression and Immune Response Analysesmentioning
confidence: 99%